Bioinspired engineering of gradient and hierarchical architecture into pressure sensors toward high sensitivity within ultra-broad working range. (September 2022) - Song, Shiqiang; Zhang, Cuifen; Li, Weizhen; Wang, Jincheng; Rao, Pinhua; Wang, Jin; Li, Tiantian; Zhang, Yong
Abstract: Introducing hierarchical microstructure on the soft material surface can effectively improve the sensitivity of the pressure sensor, however, the high sensitivity generates only at a low pressure range because of the limited compressibility of the microstructure and the incompressibility of the soft matrix. Herein, we first report a facile strategy of bioinspired engineering of hierarchical and gradient structures that can simultaneously improve the sensitivity and broaden the pressure working range. Such hierarchical and gradient structures feature hemispherical arrays and gradient pores that allow the structural deformation from tiny pressure to high pressure, significantly boosting the sensitivity over the full pressure range. By integrating these unique structures on one sensor, the sensor exhibits an ultrahigh sensitivity over a broad pressure regime (i.e., from 102.3 kPa −1 within 0–1.9 kPa to 0.34 kPa −1 within 169.6–400 kPa), a fast response time (35 ms), low limit detection (0.4 Pa) and excellent stability (>5000). The facile strategy and structure design achieve high sensitivity and broad pressure working range for an advanced pressure sensor, endowing it with wide applications, including pressure/weight monitoring, real-time human pulse wave measurements, joint motion detection and human-computer interaction. Graphical Abstract: A novel porous polymer composite with bioinspired engineering of hierarchical and gradient structures was successfully fabricated for the assembly of a flexible pressure sensor. Such hierarchical and gradient structures endowed the sensor with high sensitivity within ultra-broad working range and wide applications. ga1 Highlights: A novel type of porous PDMS composite was designed, with the integration of hierarchical and gradient architecture. Piezoresistive sensors assembled based on the porous PDMS exhibit excellent sensing performance. The sensors were further developed and applied to monitor pressure distribution, human movement, etc.